Global prevalence, characteristics, and future prospects of IncX3 plasmids: A review - Guo, Xiaobing; Chen, Ruyan; Wang, Qian; Li, Chenyu; Ge, Haoyu; Qiao, Jie; Li, Yuan (Frontiers in Microbiology, 2022)
IncX3 plasmids are narrow host range plasmids mostly found in Enterobacteriaceae with great conjugation ability, high stability, no fitness cost, and the ability to improve biofilm formation in their bacterial hosts. IncX3 plasmids have spread swiftly, primarily in several nations and among different species over the last 10 years. blaNDM, blaKPC, and blaOXA-181 are the carbapenemase genes carried by IncX3 plasmids. Among them, blaNDM is often located on the IncX3 plasmid, which is deemed as the primary vehicle of blaNDM transmission. Isolates harboring IncX3 plasmids are found in nations all over the world from human, animal, and environmental sources. Cointegrate plasmids related to IncX3 have recently been discovered to increase the antibiotic resistance spectrum and potentially broaden the host range of plasmids, restricting the use of antibiotics in the clinic. There are, however, few reviews based on the physiological and epidemiological properties of IncX3 plasmid, as well as studies on the plasmid itself. Hence, we conducted a retrospective literature review to summarize the characteristics of IncX3 plasmids aiming to provide a theoretical basis for controlling the global prevalence of IncX3 plasmids and directions for further research on the functions of the related genes on the IncX3 plasmid.